INSTITUTIONAL FORMATION OF THE MARKET FOR DEBT SETTLEMENT OF CONSUMERS OF FINANCIAL SERVICES OF CREDIT INSTITUTIONS IN UKRAINE (INNOVATIVE ECONOMY, 2020)
Khutorna M.E. INSTITUTIONAL FORMATION OF THE MARKET FOR DEBT SETTLEMENT OF CONSUMERS OF FINANCIAL SERVICES OF CREDIT INSTITUTIONS IN UKRAINEPurpose. The aim of the article is substantiation of the content of institutional measures, the implementation of which will improve the quality of assets of credit institutions of Ukraine.Methodology of research. The methodological basis of the research is formed on the basis of an institutional approach to substantiate the institutional preconditions for the functioning of the market for debt settlement of consumers of financial services of credit institutions; systematization to identify constraints and incentives for the effective use of various ways to solve the problem of non-performing bank loans; a statistical and analytical approach to quantify the level of quality of the current state of settlement of problem debt by different groups of banks in Ukraine; methods of scientific abstraction and logical generalization to describe the organizational and economic features of the formation of the market for debt settlement of consumers of financial services of different types of credit institutions of Ukraine.Findings. It is substantiated that ensuring the financial stability of credit institutions of Ukraine requires the development of a transparent market for debt settlement of consumers of financial services of credit institutions. The organizational-economic and institutional peculiarities of the formation of such a market are determined by detailing the following parameters: the legal basis of the activity of market participants; organizational form and institutional subordination of the debt management entities; administrative barriers to entry; the competitive conditions of activity of the entities for debt management and regulation of their relations with related parties; requirements for the personnel of debt management entities; the content of instruments to reduce the risks of their activities and to stimulate an increase in the volume of debt settlement of consumers of financial services of credit institutions; ways to organize debt sales; fiscal stimulus.It is proved that the most appropriate way to settle non-performing loans of state-owned banks is to involve the Deposit Guarantee Fund in this activity. This is explained by: the existence of an established mechanism for settlement of non-performing assets of liquidated banks; a well-functioning non-performing credit infrastructure that operates on the basis of transparency, uniformity of rules and public accountability; long experience of selling non-performing bank loans, including loans to related parties and corporate loans with poor quality or lack of collateral; a mechanism for independent economic investigations has been established; highly qualified specialists; no additional taxpayer spending.Originality. The institutional framework for the development of the debt management market for consumers of financial institutions of credit institutions has been improved, which, unlike the existing one, includes: substantiation of the organizational and legal framework of the activity of the debt management entity; identifying instruments for harmonizing the process of debt management from a wide range of stakeholders; disclosure of institutional and organizational features and institutional prerequisites for effective resolution of problematic debt of state-owned banks. This will help to improve the quality of consumer protection and their confidence in the monetary intermediation institution; will encourage credit institutions to improve the valuation of the market value of financial assets, including by enhancing liaison with credit bureaus.Practical value. The main provisions and conclusions of the conducted study are brought to the level of practical recommendations, take into account the current legislation and its prospective changes, and can be effectively used to solve the problems related to debt management of consumers of financial services of credit institutions in the domestic credit segment of the financial sector.Key words: credit institutions; state banks; non-performing loans; debt settlement market; debt settlement companies; institutional interaction of the entities of the debt settlement market; financial stability.
Keywords: Key words; credit institutions; state banks; non-performing loans; debt settlement market; debt settlement companies; institutional interaction of the entities of the debt settlement market; financial stability.